5‐Hydroxytryptamine promotes hepatocellular carcinoma proliferation by influencing β‐catenin. Issue 2 (30th September 2015) - Fatima, Sarwat; Shi, Xiaoke; Lin, Zesi; Chen, Guo-qing; Pan, Xiao-hua; Wu, Justin Che-Yuen; Ho, John W.; Lee, Nikki P.; Gao, Hengjun; Zhang, Ge; Lu, Aiping; Bian, Zhao Xiang
Abstract : 5‐Hydroxytryptamine (5‐HT), a neurotransmitter and vasoactive factor, has been reported to promote proliferation of serum‐deprived hepatocellular carcinoma (HCC) cells but the detailed intracellular mechanism is unknown. As Wnt/β‐catenin signalling is highly dysregulated in a majority of HCC, this study explored the regulation of Wnt/β‐catenin signalling by 5‐HT. The expression of various 5‐HT receptors was studied by quantitative real‐time polymerase chain reaction (qPCR) in HCC cell lines as well as in 33 pairs of HCC tumours and corresponding adjacent non‐tumour tissues. Receptors 5‐HT1D (21/33, 63.6%), 5‐HT2B (12/33, 36.4%) and 5‐HT7 (15/33, 45.4%) were overexpressed whereas receptors 5‐HT2A (17/33, 51.5%) and 5‐HT5 (30/33, 90.1%) were reduced in HCC tumour tissues. In vitro data suggests 5‐HT increased total β‐catenin, active β‐catenin and decreased phosphorylated β‐catenin protein levels in serum deprived HuH‐7 and HepG2 cells compared to control cells under serum free medium without 5‐HT. Activation of Wnt/β‐catenin signalling was evidenced by increased expression of β‐catenin downstream target genes, Axin2, cyclin D1, dickoppf‐1 (DKK1) and glutamine synthetase (GS) by qPCR in serum‐deprived HCC cell lines treated with 5‐HT. Additionally, biochemical analysis revealed 5‐HT disrupted Axin1/β‐catenin interaction, a critical step in β‐catenin phosphorylation. Increased Wnt/β‐catenin activity was attenuated by antagonist of receptor 5‐HT7 (SB‐258719) in HCC cell lines and patient‐derived primary tumour tissues in the presence of 5‐HT. SB‐258719 also reduced tumour growth in vivo. This study provides evidence of Wnt/β‐catenin signalling activation by 5‐HT and may represent a potential therapeutic target for hepatocarcinogenesis. Highlights: 5‐HT increases β‐catenin protein levels in serum deprived HuH‐7 and HepG2 cells. Receptor 5‐HT7 is overexpressed in 45.4% of HCC tissues. Antagonist of receptor 5‐HT7 attenuates β‐catenin protein levels in vitro and in vivo.